Insect Management in Your Florida Lawn - Eileen A. Buss; J. Bryan Unruh (EDIS, 2006)
Revised! Circular 427, a 12-page illustrated circular by Eileen A. Buss and J. Bryan Unruh, covers all aspects of insect management for Florida homeowners: monitoring, cultural practices, notes on control, precautions, and descriptions of several destructive lawn pests with information about life cycle, monitoring, damage and control for each. This version is enhanced and updated throughout, with color illustrations replacing the black-and-white line drawings of earlier versions. This publication corresponds to pages 120-130 in the Pest Management chapter of the Florida Lawn Handbook, 3rd edition. Published by the UF Department of Environmental Horticulture, August 2006.